PROTOCOL FOR A SCOPING REVIEW ON THE CONCEPTUALIZATION OF COMPETITIVE INTELLIGENCE IN ENTREPRENEURSHIP LITERATURE - Olaleye, Banji Rildwan; Emeagwali, Okechukwu Lawrence; Olasehinde, Sunday A; Oladele, Taiwo O.; Adelakun, Christo Gbenga; Ebhoaye, Solomon O. (Annals of Spiru Haret University. Economic Series, 2021)
Purpose: Competitive intelligence is a crucial skill increasingly required of entrepreneurs across firms, since guidance to enterprises on this crucial skill has proven to be problematic over the years, owing primarily to a lack of unified understanding of its meaning as well as the erroneous use of the term interchangeably with other close but dissimilar concepts. This paper aims to establish a protocol for a scoping review of relevant literature, to map, compare and synthesize the disparate conceptualizations available and relative theoretical underpinnings, in a bid to systematically derive a more robust and comprehensive definition and terminology that accurately captures all facets of the competitive intelligence concept. Methods and Analysis: This scoping review will follow the methodological recommendations first developed by Arksey and O’Malley, and subsequently refined by Levac and colleagues. A management practitioner as well as a local librarian will be involved in the development of the search strategy, and the search will be conducted in electronic databases (Web of Science, SCOPUS and EBSCO Business Complete). Ethics and dissemination: this scoping review will aid the design of upcoming studies on competitive intelligence using accurate, comprehensive and scientifically conceptualized and operationalized terminology. Results of the review will be widely distributed via journal publications and conference presentations.